2019
DOI: 10.1186/s13046-019-1222-z
|View full text |Cite
|
Sign up to set email alerts
|

BTF3 sustains cancer stem-like phenotype of prostate cancer via stabilization of BMI1

Abstract: Background Cancer stem-like traits contribute to prostate cancer (PCa) progression and metastasis. Deciphering the novel molecular mechanisms underlying stem-like traits may provide important insight for developing novel therapeutics. Methods Immunohistochemistry and immunofluorescence assays in prostatic tissues; gain- and loss-of-function analyses using ectopic overexpression and shRNAs in PCa cell lines; measurements of tumorigenic and stemness properties, and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Among the rest of the top 15 differentially methylated probes, there were several other genes that may play a role in cancer development. BMI1 is a cancer stem cell marker [ 29 ] that has been implicated in acute myeloid leukemia [ 30 ], cervical cancer [ 31 ], and prostate cancer [ 32 ], among others, by acting as a chromatic remodeler of regulatory genes. EEF1A2 expression is elevated in poor prognosis of triple negative breast cancers [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the rest of the top 15 differentially methylated probes, there were several other genes that may play a role in cancer development. BMI1 is a cancer stem cell marker [ 29 ] that has been implicated in acute myeloid leukemia [ 30 ], cervical cancer [ 31 ], and prostate cancer [ 32 ], among others, by acting as a chromatic remodeler of regulatory genes. EEF1A2 expression is elevated in poor prognosis of triple negative breast cancers [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data were confirmed from a preclinical study published by Bonnet et al in 1997 demonstrating that cells capable to generate human AML (Acute Myeloid Leukemia) in xenograft models had proliferative capacities and the ability to differentiate and self-renew indicating that normal stem cells, rather than committed progenitor cells, were the target for the neoplastic transformation [24]. Since then, the presence of CSC has been reported in several different type of tumors including breast [25], colorectal [26,27,28], prostatic [29], central nervous system cancers [30], melanomas [31] and sarcomas [32].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that Nanog and CD44 were upregulated in CTBPH1 cells as compared with vehicle-treated cells. Previous studies demonstrated that CSCs may be responsible for tumor initiation, invasion, distant metastasis, chemo-resistance, self-renewal, and differentiation potential 39 . Thus, we set out to isolate ZIC2 + cells from CTBPH1 cells and characterize the ZIC2 function.…”
Section: Discussionmentioning
confidence: 99%